Longitudinal Study of Physical Activity in Spanish Young Adolescents: Weight Status and Gender Differences - Virginia-Añez, Elizabeth; Fornieles-Deu, Albert; Sánchez-Carracedo, David (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
Past research indicates there are marked declines in physical activity (PA) during adolescence. Recent studies are offering new insights. This longitudinal study investigates changes in intensities of PA (moderate-to-vigorous vs. light), by gender and weight-status, in a sample of Spanish adolescents. Students, on average 13.9 years-old (N=833 at baseline), were followed- up a year and two years later (N=474 provided data at the three time points). Self-reported PA was recorded. Analyses revealed that PA prevalence is low, although, overtime, slight increments were observed. Girls showed higher increments in moderate-to-vigorous physical activity (MVPA); boys showed higher increments in light physical activity (LPA). Investigating by weight-status, normal-weight boys showed increments over time in LPA; no changes observed for normal-weight girls. Overweight/obese girls increased their total PA (TPA) and MVPA; overweight/obese boys increased their LPA. Underweight boys and girls decreased their TPA. Interventions targeting specific intensities of PA may be beneficial for different groups based on their gender and weight status.